THE EFFECT OF PROBLEM-BASED LEARNING INTEGRATED WITH CONCEPT MAPPING TECHNIQUE ON STUDENTS' LEARNING ACTIVITIES - Murdiyah, Siti; Suratno, S.; Nur Ardhan, Arina Firdausi (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Teachers often encountered difficulties or even failure in conducting the classroom due to the students' inability to understand the learning materials. Most students find it's challenging to associate their existing knowledge with the new one because of the learning setting that they generally have. Teachers do not consider it important to set their students for actively engaging in learning, which eventually will impact their learning outcomes. This research aimed at determining the effect of Problem-Based Learning with Concept Mapping Technique on student learning activities. This quasi-experimental study used one experimental class and one control class. The control class used STAD model. The four categories of learning activities which were measured based on active learning principles were engagement activities, cognitive skills, response to cognitive development, and response to general educational outcomes. The result showed that  Problem-based learning with concept mapping technique is proven to have a significant effect on students' activities. There were significance difference between experiment class and control class.